Psychological interventions for chronic non-specific low back pain: protocol of a systematic review with network meta-analysis - Lingxiao Chen; Jill Hayden; Manuela Ferreira; Emma Ho; Milena Simic; Claire Ashton-James; Josielli Comachio; Paulo Ferreira (BMJ Open)
Introduction Psychological factors such as fear avoidance beliefs, depression, anxiety, catastrophic thinking and familial and social stress, have been associated with high disability levels in people with chronic low back pain (LBP). Guidelines endorse the integration of psychological interventions in the management of chronic LBP. However, uncertainty surrounds the comparative effectiveness of different psychological approaches. Network meta-analysis (NMA) allows comparison and ranking of numerous competing interventions for a given outcome of interest. Therefore, we will perform a systematic review with a NMA to determine which type of psychological intervention is most effective for adults with chronic non-specific LBP.Methods and analysis We will search electronic databases (MEDLINE, Embase, PsycINFO, Cochrane Central Register of Controlled Trials, Web of Science, SCOPUS and CINAHL) from inception until 22 August 2019 for randomised controlled trials comparing psychological interventions to any comparison interventions in adults with chronic non-specific LBP. There will be no restriction on language. The primary outcomes will include physical function and pain intensity, and secondary outcomes will include health-related quality of life, fear avoidance, intervention compliance and safety. Risk of bias will be assessed using the Revised Cochrane risk-of-bias tool for randomised trials (RoB 2) tool and confidence in the evidence will be assessed using the Confidence in NMA (CINeMA) framework. We will conduct a random-effects NMA using a frequentist approach to estimate relative effects for all comparisons between treatments and rank treatments according to the mean rank and surface under the cumulative ranking curve values. All analyses will be performed in Stata.Ethics and dissemination No ethical approval is required. The research will be published in a peer-reviewed journal.PROSPERO registration number CRD42019138074.